Half-inhibition concentrations of new cholinesterase inhibitors - Zdrazilová, Pavla; Stepánková, Sárka; Komers, Karel; Ventura, Karel; Cegan, Alexander (Zeitschrift fur Naturforschung. C, Journal of biosciences, 2004)
The power of chosen carbamates and hydrazinium derivatives (carbazates) to inhibit the hydrolysis of acetylthiocholine by butyrylcholinesterase or acetylcholinesterase was tested. The determined pI50 values (= negative logarithm of the molar concentration inhibiting the enzyme activity by 50%) of the tested substances were compared with pI50 values of the commercially used drugs for the Alzheimer's disease treatment--rivastigmine and galanthamine.
Keywords: Animals; Butyrylcholinesterase; Horses; butyrylcholinesterasa; karbamáty; Kinetics; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; Carbamates; kinetika; koně